2021
DOI: 10.1161/jaha.121.022588
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Time After Stroke and Exercise Training Outcomes: A Meta‐Regression Analysis

Abstract: Background Knowledge gaps exist regarding the effect of time elapsed after stroke on the effectiveness of exercise training interventions, offering incomplete guidance to clinicians. Methods and Results To determine the associations between time after stroke and 6‐minute walk distance, 10‐meter walk time, cardiorespiratory fitness and balance (Berg Balance Scale score [BBS]) in exercise training interventions, relevant studies in post‐stroke populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 211 publications
0
9
0
Order By: Relevance
“…It should be noted that the differences in demographic indices including age and post-injury time may influence the efficacy of rehabilitation treatments [43,50,51]. However, to our surprise, the meta-regression showed that the mean age was not a significant predictor of effect size for the outcome parameters in this review.…”
Section: Discussionmentioning
confidence: 53%
“…It should be noted that the differences in demographic indices including age and post-injury time may influence the efficacy of rehabilitation treatments [43,50,51]. However, to our surprise, the meta-regression showed that the mean age was not a significant predictor of effect size for the outcome parameters in this review.…”
Section: Discussionmentioning
confidence: 53%
“…These meta-regressions were attempted only when there were at least 10 available studies and (for categorical independent variables) at least 3 studies in each category 2. When there were sufficient studies, the primary analysis was stratified by stroke chronicity (the first meta-regression variable above) based on the aims of this study and established differences in effect sizes between subacute and chronic stroke studies 28. Additional meta-regressions were attempted only within chronicity subgroups to avoid likely confounding.…”
Section: Methodsmentioning
confidence: 99%
“…2 When there were sufficient studies, the primary analysis was stratified by stroke chronicity (the first meta-regression variable above) based on the aims of this study and established differences in effect sizes between subacute and chronic stroke studies. 26 Additional meta-regressions were only attempted within chronicity subgroups to avoid likely confounding.…”
Section: Between-study Heterogeneity Meta-regression and Assessment O...mentioning
confidence: 99%